Insects of the Subfamily Scolytinae (Insecta: Coleoptera, Curculionidae) Collected with Pitfall and Ethanol Traps in Primary Forests of Central Amazonia - Raimunda Liege Souza de Abreu; Greicilany de Araújo Ribeiro; Bazilio Frasco Vianez; Ceci Sales-Campos (Psyche: A Journal of Entomology)
An experiment was conducted in a primary forest area of the Tropical Forest Experimental Station, 45 km from Manaus-Boa Vista Highway, in order to compare the insect fauna of the subfamily Scolytinae, in flight activity and on the ground. Five impact traps of the type Escolitideo/Curitiba, with ethanol baits, were installed at the height of 3 m above the ground, and five pitfall traps were buried in the same area of the above ground traps. The data collections were evaluated through abundance, richness, and Simpson diversity index, and, to compare these data with the pitfalls and the months collection, the ANOVA was used. The Pearson correlation test was also carried out to evaluate the meteorological factors (temperature and rainfall). From the total of 2,910 Scolytinae, 2,341 were captured in pitfall traps representing 80.45% and 569 with Escolitideo/Curitiba traps representing 19.55%. The most abundant species in the collections were Xyleborus volvulus Fabricius and Xyleborus affinis Eichhoff, and this was classified as constant in both habitats. The result of the analysis indicates that the Simpson’s index was high and that the abundance of insects was affected by the types of trap and by the month of collection. The analysis of correlation with meteorological factors showed that only Xyleborus spinulosus species presented significant correlation with temperature.